The early warning systems about landslide hazards in Ukraine - Sirenko, Anatolii P. (Kyiv National University of Construction and Architecture, 2021)
Early warning systems are an effective tool for preventing and mitigating the risks associated with the occurrences of various types of threats (including landslides). The paper presents and describes the concept and practical implementation of the new integrated methodology for early warning systems based on the integration of modern monitoring technologies and comprehensive numerical modeling of an object under study. Designing, testing and operation of monitoring systems of complex and unique construction objects have a lot of difficulties, need system knowledge in several spheres of science and engineering: construction, informational technologies, measuring instruments, systems and algorithms of data processing, programming etc. This information is known only to narrow range of highly qualified specialists that directly participated in designing and installing of the particular monitoring system at the particular construction object. The basic concept of Early Warning System installed on landslides is that the elements at risk, especially people being close from the dangerous area, must have sufficient time to evacuate, if an imminent collapse is expected. Therefore, an effective Early Warning System shall include such four main sets of actions: monitoring of the activity of the observed object, i.e. the data collection and transmission, as well as the equipment maintenance; the analysis and modeling of the observed and studied object; warning, i.e. the dissemination of simple and clear information about the observed object; the effective response of risk exposed elements; full understanding of risks. The examples of the practical application of the proposed integrated methodology to various construction projects and natural and technological systems are given, including 1) Central Livadia Landslide System and Livadia Palace; 2) a system for landslide hazard areas monitoring in the Kharkiv region; and 3) landslides Early Warning System using unmanned aerial vehicles as a specialized monitoring system for shearing deformations.